The Hound of the Baskervilles : Histoire, fantasme et genèse de la narration policière - Christophe Gelly (Sillages Critiques)
Through one of the most famous Sherlock Holmes stories, we can shed light on some typical features in the narrative system of detective stories, especially concerning Watson as an unreliable narrator, once more fooled by Sherlock Holmes here in many chapters on end. More precisely, we deal with the main fantasy conveyed through the text, i.e. the fear of being devoured by the frightful Hound embodying the Baskerville legend, and we try to identify the grounds and the impact of such a fantasy. Lastly, we study the character of Sherlock Holmes himself, his behaviour and his strategy when facing this fantasy of an engulfed self, so as to suggest our own vision of the most famous ever fictional detective.